2006
DOI: 10.1002/aqc.758
|View full text |Cite
|
Sign up to set email alerts
|

Is the decline of freshwater mussel populations in a regulated coastal river in south‐eastern Australia linked with human modification of habitat?

Abstract: ABSTRACT1. The Hawkesbury-Nepean River provides potable water for 5 million people living in the Sydney basin, and water for agricultural and horticultural production that meets most of Sydney's daily needs for fresh food. Anecdotal evidence indicated that numbers of freshwater mussels have seriously declined in much of the river over recent decades.2. A field survey revealed the presence of populations of three species of mussels, Hyridella depressa, Hyridella australis and Velesunio ambiguus in the river. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…Previous research identified mussel distribution patterns that showed a high level of correlation with geomorphic reach type (Brainwood et al, 2006;Brainwood, in press). To explore this relationship further, the second stage of analysis involved examining data separately within geomorphic reach types.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous research identified mussel distribution patterns that showed a high level of correlation with geomorphic reach type (Brainwood et al, 2006;Brainwood, in press). To explore this relationship further, the second stage of analysis involved examining data separately within geomorphic reach types.…”
Section: Discussionmentioning
confidence: 96%
“…Density of mussels was not normally distributed, and density of mussel size classes within these sites showed a right skewed distribution characteristic of mussel populations examined in the Hawkesbury-Nepean River Table 1. Results of hypotheses testing using forward stepwise logistic regression for presence/absence of mussel assemblages in the Hawkesbury-Nepean River with substrate characteristics (Brainwood et al, 2006;Brainwood, in press). Data were characterized by high numbers of zeros recorded for mussel densities at sites sampled.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations